Adaptation and mitigation actions for flood management - Delgado Moreira, Maria Isabel (2024)
In order to generate information that facilitates decision-making concerning adaptation and mitigation actions related to planning for flood management, this study assessed the risk of flooding in the Garrapata microbasin, located in Chone, Ecuador, using a multi-criteria analysis based on GIS modelling. The technique involved choosing conditioning factors, which included secondary data and satellite photos. These were then processed using QGIS to produce theme maps of isohyets, river distance, elevation, slope, soil texture, and land use and cover. These maps were weighted using the Analytical Hierarchy Process (AHP) to give distinct weights to each factor, producing a flood risk map that was validated with Google Earth Engine. The findings indicated that low plains spanning 12.64 km² close to the Garrapata River are at high risk of flooding as a result of heavy rainfall or overflows. This analysis shows that the use of AHP and GIS together is a useful technique for determining flood risk and providing essential data for decision-making, which helps build more resilient communities that are better equipped to handle flood-related disasters.